THE TRANSNATIONAL INSTITUTIONAL DIALOGUE IN BELO MONTE CASE - de Araújo, Luis Cláudio Martins (REVISTA DA AGU, 2015)
This article aims to discuss the relationship between the Supreme Court of Brazil and the Inter-American Commission on Human Rights, especially in Belo Monte Dam Case, bearing in mind that when disagreements occur States must cooperate to avoid transboundary or global environmental problems. The classic concepts of nation-state sovereignty resulted from the Peace of Westphalia in 1648 and the permanent Sovereignty over Natural Resources based on territorial integrity and the right to self-determination and non-intervention of the States is guaranteed by the main international instruments. Similarly, the International Environmental Law, structured on the unquestionable right of an ecological balance, is a standard to be followed by the international community to guarantee that environmental damages do not cause harm to areas beyond the limits of the State. Thus the States have the sovereign right over it owns resources, but have also the responsibility to ensure the environment protection. Therefore, this essay intends to demonstrate, particularly under the influence of Jeremy Waldron, Rosalind Dixon, John Rawls and Ju?rgen Habermas conceptions, that in the Belo Monte Dam Case, the dialogue between Domestic and International institutions according to the international cooperation is mandatory to guarantee coherence and unity to the new millennium international system.